Los repositorios de datos de investigación en la era de la ciencia abierta: un análisis comparativo: Research data repositories in the era of open science: a comparative analysis - Avila Barrientos, Eder (Revista General de Información y Documentación, 2024)
Research data repositories are systems that facilitate open access to research data, allowing researchers around the world to access it in various contexts; encourage the reuse of research data, which can lead to new scientific discoveries and technological advances; They help preserve research data over the long term, ensuring it is available to future generations of researchers. In recent years, there has been a significant increase in the number of research data repositories, so it is essential to know their attributes and understand their implementation in the digital environment. Therefore, the objective of this work is to analyze the similarities and differences of research data repositories based on the criteria established by the open science movement.